Initial experience of spatially fractionated lattice radiation therapy for palliative treatment of pediatric bulky tumors - Zhang, Hualin; Wong, Kenneth; Olch, Arthur; Han, Hye Ri; Chau, Brittney; Lukas, Lauren; Chang, Eric L. (Frontiers in Oncology, 2025)
PurposeSpatially fractionated radiation therapy (SFRT) has demonstrated high clinical response rates with minimal toxicity in adult patients with bulky tumors, including radioresistant histologies. However, there is limited clinical data on SFRT in pediatric patients, and optimal techniques and dose regimens remain unclear. This study presents our single-institution experience with SFRT for the palliative treatment of bulky pediatric tumors.Methods and materialsA retrospective review was conducted on six pediatric patients with metastatic or unresectable bulky tumors treated with SFRT. SFRT was delivered using VMAT in the form of Lattice Radiation Therapy (LRT). SFRT fraction doses ranged from 10–15 Gy, with 7–26 high-dose vertices per treatment. Sequential conventional external beam radiation therapy was delivered in 6 courses (67%), and SFRT was used for re-irradiation in 3 courses (33%). A radiobiological modeling approach was employed to estimate treatment effects across varying cancer and normal cell radiosensitivity levels.ResultsSix pediatric and young adult patients (median age: 10 years) received in total 9 SFRT courses. Tumor sites included the liver (4), abdomen (3), pelvis (1), and thorax (1), with a median gross tumor volume of 666 cc. Median follow-up was 1.7 months. Tumor volume reductions were observed in 67% of treated sites (mean reduction: 279.3 cc), with significant clinical improvements in symptoms (e.g., pain, gastrointestinal symptom relief) and no grade 3 or higher toxicities. Radiobiological modeling data indicates that SFRT improves the therapeutic ratio, particularly when cancer cells are radioresistant and surrounding normal tissues are radiosensitive. Increasing the number of high-dose cores may further enhance this ratio.ConclusionsSFRT seems to be a safe and effective palliative treatment for pediatric bulky tumor patients in our preliminary study. Radiobiologic modeling suggests that increasing the density of high-dose cores can enhance the therapeutic ratio, potentially reducing normal tissue toxicity.